Health, nutrition, and development of children born preterm and low birth weight in rural Rwanda: a cross-sectional study - Catherine M. Kirk; Jean Claude Uwamungu; Kim Wilson; Bethany L. Hedt-Gauthier; Neo Tapela; Peter Niyigena; Christian Rusangwa; Merab Nyishime; Evrard Nahimana; Fulgence Nkikabahizi; Christine Mutaganzwa; Eric Ngabireyimana; et al. (BMC, 2017)
Abstract Background As care for preterm and low birth weight (LBW) infants improves in resource-limited settings, more infants are surviving the neonatal period. Preterm and (LBW) infants are at high-risk of nutritional and medical comorbidities, yet little is known about their developmental outcomes in low-income countries. This study evaluated the health, nutritional, and developmental status of preterm/LBW children at ages 1-3 years in Rwanda. Methods Cross-sectional study of preterm/LBW infants discharged between October 2011 and October 2013 from a hospital neonatal unit in rural Rwanda. Gestational age and birth weight were gathered from hospital records to classify small for gestational age (SGA) at birth and prematurity. Children were located in the community for household assessments in November-December 2014. Caregivers reported demographics, health status, and child development using locally-adapted Ages and Stages Questionnaires (ASQ-3). Anthropometrics were measured. Bivariate associations with continuous ASQ-3 scores were conducted using Wilcoxon Rank Sum and Kruskal Wallis tests. Results Of 158 eligible preterm/LBW children discharged from the neonatal unit, 86 (54.4%) were alive and located for follow-up. Median birth weight was 1650 grams, median gestational age was 33 weeks, and 50.5% were SGA at birth. At the time of household interviews, median age was 22.5 months, 46.5% of children had feeding difficulties and 39.5% reported signs of anemia. 78.3% of children were stunted and 8.8% wasted. 67.4% had abnormal developmental screening. Feeding difficulties (p = 0.008), anemia symptoms (p = 0.040), microcephaly (p = 0.004), stunting (p = 0.034), SGA (p = 0.023), very LBW (p = 0.043), lower caregiver education (p = 0.001), and more children in the household (p = 0.016) were associated with lower ASQ-3 scores. Conclusions High levels of health, growth, and developmental abnormalities were seen in preterm/LBW children at age 1-3 years. As we achieve necessary gains in newborn survival in resource-limited settings, follow-up and early intervention services are critical for ensuring high-risk children reach their developmental potential.